THE IMPACT OF CLIMATE CHANGE ON THE AGROECOLOGICAL CONDITION OF IRRIGATED SOILS IN KHOREZM REGION - Aminov, Bexzod Bahramovich; Okhunjanova, Dildora Kamiljonovna; Bazarbayeva, Muhsina Quvondikovna; Abdullayeva, Mehribon Atabekovna (ILIM hám JÁMIYET, 2026)
The article analyzes the main agroecological processes occurring in the irrigated soils of the Khorezm region under conditions of global climate change. Based on scientific sources, the impacts of rising air temperatures, changes in precipitation patterns, and water resource scarcity on soil salinization, fertility decline, and degradation processes are examined. The research findings contribute to the development of practical recommendations for the sustainable use of land resources in the region.